The Impact of the Division of Muaro Kiawai Barat Nagari on Governance in Gunung Tuleh Subdistrict, West Pasaman Regency - Melani Yunanda; Sinta Westika Putri (LP3M KH Yazid Karimullah Institute, 2026)
The division of nagari is a decentralization policy aimed at improving the effectiveness of governance, bringing public services closer to the community, and accelerating development and community empowerment. However, the implementation of this policy does not always have the same impact on every area resulting from the division. This study aims to analyze the impact of the division of Muaro Kiawai Barat Nagari on governance in Gunung Tuleh Subdistrict, West Pasaman Regency, and to identify the challenges faced following the division. The study employs a qualitative approach using a descriptive research design. Research informants were selected using purposive sampling. Data were collected through interviews, observations, and documentation, then analyzed using qualitative data analysis techniques with validity testing through source triangulation. The results of the study indicate that the village division has had a positive impact on governance, as evidenced by increased accessibility of public services to the community, development initiatives that are more responsive to community needs, enhanced community development efforts, and the implementation of community empowerment programs. On the other hand, there are still negative impacts in the form of development constraints due to limited budgets and the lack of optimal sustainability of community empowerment programs because Nagari-Owned Enterprises (BUMN) have not yet been established. The main challenges faced by the nagari government are budget constraints and the suboptimal management of community empowerment programs.